WSCUC Substantive Change Program Screening Form (2024)
Institutions planning to implement new degree programs beginning on or after July 1, 2017 should submit this screening form to WSCUC to determine if a Substantive Change review and approval is necessary prior to implementation. A determination on the necessity of review is made after submission of the form and any further information requested by WSCUC. The form should be submitted to John Hausaman (jhausaman@wscuc. org).